Political consequences of the tidal wave in Indonesia and Sri Lanka - Kay Moeller; Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2005)
The tidal wave that originated near Indonesia's Sumatra island on 26 December 2004 killed more than 170,000 people in Indonesia, Malaysia, Thailand, Burma, Sri Lanka, India, and the Maldives. International pledges to generously contribute to the reconstruction effort have inspired new hopes for a settlement of decades-old civil wars in Indonesia and Sri Lanka. Whereas positive developments in both states cannot be ruled out, it remains doubtful whether international aid can provide a basis for lasting conflict solutions. (SWP Comments / SWP)
Keywords: 320